"That is my farm" – An integrated co-learning approach for whole-farm sustainable intensification in smallholder farming. (March 2021) - Marinus, Wytze; Descheemaeker, Katrien K.E.; van de Ven, Gerrie W.J.; Waswa, Wycliffe; Mukalama, John; Vanlauwe, Bernard; Giller, Ken E.
Abstract: The use of options for sustainable intensification of smallholder farming in sub-Saharan Africa is often limited by knowledge and resource constraints. To address both constraints, we developed and tested an integrated co-learning approach to improve farm level productivity. The approach was tested by differentiating a group of co-learning farmers and a group of comparison farmers in two locations in western Kenya during five seasons. Both groups received a US$ 100 voucher each growing season and the co-learning group also took part in co-learning activities. The integrated co-learning approach was comprised of four complementary elements: input vouchers, an iterative learning process, common grounds for communication, and complementary knowledge. Central to the approach were co-learning workshops before each season. Workshop topics built on topics from previous seasons and on farmers' feedback and researchers' observations. Activities during each season included farm management monitoring, yield measurements and evaluation interviews. This resulted in multiple learning loops for both farmers and researchers. The voucher fostered learning through increased and diversified input use. For instance, intercropped legumes were smothered by the prolific growth of maize resulting from increased fertilizer use. After setting up joint demonstrations, farmers started to use alternative spacing options for intercropping. Building common ground on concepts and processes governing farm system functioning fostered a deeper understanding by farmers on the suitability of options to their farm and by researchers on locally relevant content. Soil fertility gradients was such a concept through which judicious use of fertilizers was discussed. After five seasons, co-learning farmers had a more diverse and cohesive knowledge of their farm than comparison farmers. Co-learning farmers highlighted farm level management options, management of the parasitic weed striga and options for integrated soil fertility management as the most important things they learned. A tangible learning outcome was the continued increase in groundnut and soybean area among co-learning farmers, which led to more diversified maize cropping systems. We attribute these differences to the co-learning process. Our results demonstrate how the integrated co-learning approach changed both knowledge and practices of participating farmers and researchers. The amplifying effects of the four key elements appeared to be important for enabling sustainable intensification of smallholder farming systems. Graphical abstract: Unlabelled Image Highlights: We developed and tested an integrated co-learning approach. The approach combined input vouchers and iterative learning on sustainable intensification. Co-learning farmers had a more diverse and cohesive knowledge after five seasons. Co-learning farmers increased the share of legumes in their cropping system.